Paradoxical Activation of Oncogenic Signaling as a Cancer Treatment Strategy - Dias, Matheus Henrique; Friskes, Anoek; Wang, Siying; Fernandes Neto, Joao M.; van Gemert, Frank; Mourragui, Soufiane; Papagianni, Chrysa; Kuiken, Hendrik J.; Mainardi, Sara; Alvarez-Villanueva, Daniel; Lieftink, Cor; Morris, Ben; et al. (American Association for Cancer Research (AACR), 2024)
Cancer homeostasis depends on a balance between activated oncogenic pathways driving tumorigenesis and engagement of stress response programs that counteract the inherent toxicity of such aberrant signaling. Although inhibition of oncogenic signaling pathways has been explored extensively, there is increasing evidence that overactivation of the same pathways can also disrupt cancer homeostasis and cause lethality. We show here that inhibition of protein phosphatase 2A (PP2A) hyperactivates multiple oncogenic pathways and engages stress responses in colon cancer cells. Genetic and compound screens identify combined inhibition of PP2A and WEE1 as synergistic in multiple cancer models by collapsing DNA replication and triggering premature mitosis followed by cell death. This combination also suppressed the growth of patient-derived tumors in vivo. Remarkably, acquired resistance to this drug combination suppressed the ability of colon cancer cells to form tumors in vivo. Our data suggest that paradoxical activation of oncogenic signaling can result in tumor-suppressive resistance.